Guatemala. Reflections on the Social Movement - Cuevas-Molina, Rafael (2016)
The #RenunciaYa movement, Spa-nish for “Resign Now,” that led to the resignation of the president and vice president of Guatemala, is similar n many ways to movements in other parts of Latin America and the world. However, as with all social movements, it also has a series of defining charac-teristics that derive from historical and cultural factors, and from the country’s recent socio-political dynamic. Two other factors are taken into account when analyzing the movement: an external factor that is the United States of America, with impor-tant geostrategic interests in the region, and the self-interested participation of people and groups of the Guatemalan bourgeoisie.